(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
In Today’s fast moving world automobile is the main mode of transport and its safety is concerned most. So, we have selected to do Analysis and Optimization of Disc Brake Rotor to increase the performance of disc brake rotor. Generally Disc Brake Rotor is manufactured by using the materials Cast Iron, Aluminum, steel, composite ceramics, silica carbide. Goal is to Get high performance Disc Brake Rotor by analyzing and manufacturing the disc brake rotor by using different material. Disc Brake Rotor model is designed and analyzed in CAD /CAM packages (Pro-e and Ansys). Disc Brake Rotor is the main part of a braking system in automobile, as pads in braking system are rubbed against the brake rotor to create friction and there by stopping the vehicle. So, in this project main aim is to design the Disc Brake Rotor which gives high performance than the present disc brake rotor.